The Validity of Informed Refusal With Elements of Forced Discharge of COVID-19 Patients From Hospitals, as Reviewed in Accordance With Law No. 29 of 2004 on Medical Practices, in Conjunction With Law No. 4 of 1984 on the Prevention of Infectious Diseases - Purwanto, Agus; Ginting, James Davidta (Sinergi International Journal of Law, 2023)
Health is a vital aspect of human life. Covid-19 has had a significant impact on the Indonesian population, particularly on their health. During this period, the healthcare profession has come under intense scrutiny due to its direct involvement in healthcare. In the management of the Covid-19 pandemic, challenges have arisen, notably the high number of patients or their families requesting forced discharge before recovery. The research problem and objectives revolve around the validity of informed refusal with elements of forced discharge at the request of Covid-19 patients from hospitals and the legal consequences for both patients and doctors. The research methodology employed is empirical juridical, with primary data collected through questionnaires at a private hospital in West Jakarta, complemented by references from various sources, including books, journals, and legal regulations. Data analysis was conducted using a qualitative normative approach. The research findings indicate that cases of forced discharge following a Covid-19 diagnosis persist despite the existence of regulations such as the Health Law and the Law on the Prevention of Infectious Diseases. In conclusion, informed refusal does not constitute an agreement but rather a unilateral statement by the patient to the hospital and/or doctor. Consequently, full responsibility lies with the patient, as there are currently no regulatory provisions or prohibitions allowing patients to voluntarily leave the hospital, even if the patient's condition has not been assessed as fully recovered by the hospital or doctor.